Relationship between athletes` history of stressors and sport injury: A systematic review and meta-analysis - Chyi, T.; Lu, F. J. H.; Hsieh, Y.-C.; Hsu, Y.-W.; Gill, D. L.; Fang, B.-B. (Perceptual and Motor Skills, 2024)
A history of stressors in athletes represents psychosocial factors that may lead to sport injury. However, empirical studies have provided varying results for the relationship between stress history and sport injury. We examined prior literature on the stress history - sport injury relationship within a systematic review and, by meta-analysis, we offered a pooled estimate of the strength of this relationship. We searched seven major academic databases (Sportdiscus, Psyinfo, Academic Search Premier, Ovid, Scopus, Web of Science, and PubMed) from January 2000 to September 2023 and identified 19 empirical studies that examined injuries in sports contexts for meta-analysis. In 19 empirical studies of moderate to high publication quality, we found moderate heterogeneity (Q(17) = 98.61; p < .001), low sensitivity (I2 77.82-83.77), and low publication bias (Z-value = 7.74; p < .001). Further, using a random effect estimate-r, we found a low but significant correlation between stress history and sport injury, yielding a small overall effect size (ES) of r = .12. Furthermore, moderation analyses found adolescents (r = .14), contact-sport athletes (r = .09), non-elite athletes (r = .13), and non-European athletes (America r = .16; Asia r = .14; Oceania r = .14) to have a relatively higher ES than their counterparts in this stress history/sport injury relationship. We concluded that inevitable life stressors may lead to many negative consequences for athletes, such that sports professionals should provide stress management educational programs to enhance athletes` health and well-being.